2011
DOI: 10.1063/1.3601462
|View full text |Cite
|
Sign up to set email alerts
|

Graphene network on indium tin oxide nanodot nodes for transparent and current spreading electrode in InGaN/GaN light emitting diode

Abstract: We report a device that combines indium tin oxide (ITO) nanodot nodes with two-dimensional chemically converted graphene (CCG) films to yield a GaN-based light emitting diode (LED) with interesting characteristics for transparent and current spreading electrodes for the potential use in the ultraviolet region. The current-voltage characteristics and electroluminescence output power performance showed that CCG network on ITO nanodot nodes operated as a transparent and current spreading electrode in LED devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 18 publications
0
25
0
2
Order By: Relevance
“…Note that, prior to the graphene transfer, the surfaces of the GaN wafers were cleaned with acetone, isopropyl alcohol, H 2 SO 4 :HCl (1:1) solutions, a buffered oxide etchant, and deionized water. The detailed synthesis of graphene by the CVD method and transfer techniques can be found elsewhere [24][25][26][27]36] (also shown in Fig. S1 in the Electronic Supplementary Material (ESM)).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that, prior to the graphene transfer, the surfaces of the GaN wafers were cleaned with acetone, isopropyl alcohol, H 2 SO 4 :HCl (1:1) solutions, a buffered oxide etchant, and deionized water. The detailed synthesis of graphene by the CVD method and transfer techniques can be found elsewhere [24][25][26][27]36] (also shown in Fig. S1 in the Electronic Supplementary Material (ESM)).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, Chandramohan et al [23] showed that the specific contact resistance of a graphene contact formed on heavily Mg-doped p-GaN was as large as ~10 -1 Ω·cm 2 . To overcome this poor p-Ohmic contact, a hybrid-type contact combining graphene with indium-tin-oxide islands [24], Au nanoparticles [25], Ag nanowires [26], and Ag nanocluster [27] has been introduced by our groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Other solutions include using interlayers of thin metal 13,14 or ITO nanodots. 15 Nevertheless, these attempts were all at the expense of losing transparency (e.g., merely 78% for 1 nm Ni/1 nm Au/monolayer graphene). 14 We note that optical transmission is ultra important for LEDs.…”
mentioning
confidence: 99%
“…Many researches have tried to solve this problem by using spreading layers [17][18][19]. Until now, indium-tin-oxide (ITO) has been used broadly as a current spreading layer for its transparency and low resistance [20][21][22]. Although the ITO in the LED device makes current spread widely toward the active region, however, the non-uniformity of current spreading has not been solved completely [23,24].…”
Section: Introductionmentioning
confidence: 99%